Green open space planning based on spatial justice in Jakarta: Study of child friendly integrated public spaces/RPTRA and general green open space - Ramadhan, Aswin Kurnia; Saputra, Erlangga (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: Urbanization has significantly reduced green open spaces in Jakarta, impacting ecological balance and quality of life. While the importance of green open spaces for urban quality of life is well understood, comprehensive studies on spatial justice related to the distribution and accessibility of green open spaces in major cities like Jakarta are still limited. This study aims to assess the distribution, accessibility, and government budget allocation for public green open spaces in South Jakarta, with a focus on spatial justice and equitable access. Method: Using GIS software, this study assesses the distribution and accessibility of urban green spaces, conducts descriptive analysis on government budget allocation, and evaluates justice in public green space planning in South Jakarta. Findings: Despite the overall availability of green open space in South Jakarta meeting the standard of 0.2 m²/capita, the sub-districts of Pasar Minggu and Pesanggrahan still exhibit gaps in availability, and accessibility uneven trough all South Jakarta. Conclusion: Moreover, the budget allocated by the government for green spaces is relatively low compared to the total budget of DKI Jakarta. Green open space planning in the City of South Jakarta has not yet fully achieved spatial justice. This is influenced by the insufficient number, area and distribution to reach all regions and accommodate all levels of society. Novelty/Originality of This Article: This study highlights spatial injustice in the distribution and accessibility of green open spaces in South Jakarta using GIS analysis, revealing disparities despite meeting per capita standards and inadequate government budget allocation.